Administrative culture in India - Sharma, R. D., 1937- (New Delhi : Anamika Publishers & Distributors, 2000)
Contributed articles presented at a regional conference held in 1996
Includes bibliographical references
Keywords: Public administration -- India; India -- Politics and government -- 1977-